Stress induced ordering due to interstitial elements in Nb and Ta by frequency analysis - Grandini, Carlos Roberto [UNESP]; Shukla, M. M. (Editions Physique, 1996)
It is well known that the interstitial elements present in solid solution in metals interact with the matrix by a relaxation process known as stress induced ordering. Traditionally this relaxation process is observed in the internal friction measurements. It is a common practice that researchers present the results of the frequency together with internal friction without giving any analysis. In this work we apply an expression which relates the variation of frequency with temperature and analyse the experimental results cited in the literature of the relaxation process due to the stress induced ordering of oxygen and nitrogen present in niobium and tantalum.